2017
DOI: 10.3390/mi8070204
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic and Nanofluidic Resistive Pulse Sensing: A Review

Abstract: The resistive pulse sensing (RPS) method based on the Coulter principle is a powerful method for particle counting and sizing in electrolyte solutions. With the advancement of micro- and nano-fabrication technologies, microfluidic and nanofluidic resistive pulse sensing technologies and devices have been developed. Due to the unique advantages of microfluidics and nanofluidics, RPS sensors are enabled with more functions with greatly improved sensitivity and throughput and thus have wide applications in fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 148 publications
0
51
0
Order By: Relevance
“…Tunable resistive pulse sensing can also be used to investigate adsorbed protein layers on nanoparticles by individual particle size measurement 119 , which is not possible using conventional techniques such as dynamic light scattering due to the formation of agglomerates. It should be noted that the sensitivity and throughput of resistive pulse sensing is still improving, especially with the integration of micro-and nano-fabrication technologies 120 . Figure 9.…”
Section: Direct Analysis Of Nanoparticle Suspensionsmentioning
confidence: 99%
“…Tunable resistive pulse sensing can also be used to investigate adsorbed protein layers on nanoparticles by individual particle size measurement 119 , which is not possible using conventional techniques such as dynamic light scattering due to the formation of agglomerates. It should be noted that the sensitivity and throughput of resistive pulse sensing is still improving, especially with the integration of micro-and nano-fabrication technologies 120 . Figure 9.…”
Section: Direct Analysis Of Nanoparticle Suspensionsmentioning
confidence: 99%
“…The detection and analysis of single molecules with nanopipettes relies on the principle of resistive pulse sensing. [7,11,12] The single-molecule sensitivity of this approach has led to the adoption of nanopipettes in many label-free and carrier-based single biomolecule detection, delivery and biosensing applications. [8][9][10] This field drives the molecule of interest through the nanopipette pore, which, if is of similar size as the Stokes diameter of the molecules, results in a short but easily detectable pulse in an otherwise steady ionic current.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed reviews about impedance pulse sensing can be found from other review papers. 41,[59][60][61][62][63] Despite the differences in analyte recognition principles, if an electrical biomarker sensing array is used, each array needs to differentiate signals from individual sensors/sensing channels via signal processing/multiplexing strategies. In this paper, we focus on reviewing various multiplexing strategies (i.e., spatial/time/frequency/codes/particle-based multiplexing) aiming at detection of various biomarkers (i.e., nuclear acids, macromolecular biomarkers/proteins, and cells).…”
Section: Electrical Biomarker Detection Methodsmentioning
confidence: 99%